2007
DOI: 10.1157/13108503
|View full text |Cite
|
Sign up to set email alerts
|

Costes y patrón de uso de servicios en pacientes que demandan atención por problemas mentales en asistencia primaria

Abstract: Outpatients seeking care for some type of MD had a high number of comorbidities and showed greater annual cost per patient in the primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…The heterogeneity of the percentages may largely be due to the diagnostic classification criteria, the instruments used or the country where the study is carried out. Using a Spanish population, other studies have also found higher levels, of between 20 and 50% ( Sicras-Mainar et al, 2007 ). Be the figures as they may, researchers commonly conclude that emotional disorders amongst health service patients tend to be underestimated.…”
Section: Discussionmentioning
confidence: 84%
“…The heterogeneity of the percentages may largely be due to the diagnostic classification criteria, the instruments used or the country where the study is carried out. Using a Spanish population, other studies have also found higher levels, of between 20 and 50% ( Sicras-Mainar et al, 2007 ). Be the figures as they may, researchers commonly conclude that emotional disorders amongst health service patients tend to be underestimated.…”
Section: Discussionmentioning
confidence: 84%
“…Según las proyecciones de la OMS para 2020 alcanzarán el 15% del total, llegando a ser la depresión la segunda causa de morbilidad, por detrás de la cardiopatía isquémica 9 . Actualmente, un 20-25% de los pacientes que consultan en AP presentan síntomas relacionados con los trastornos mentales [23][24][25] .…”
Section: Introductionunclassified
“…This has to do not only with the heterogeneity of social care needs, but principally with other more structural features that constrain reform, mainly the still limited political visibility of reform which decentralisation helps to curb. Yet, still to date the percentage of individuals that use primary mental health care is lower than in most European countries (Sicras Mainar et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%